On the Amphipod Mentopa groenlandica H. J. HANSEN found in the mantle cavity of the Lamellibranchiate Pandora glacialis LEACH in East Greenland - Stephensen , K.; Thorson, G. (Meddelelser om Grønland, 2026)
Not applicable.